Prevalence of interarm blood pressure difference is notably higher in women; the Viborg population-based screening program (VISP) - Marie Dahl; Jesper Winkler Andersen; Jes Lindholt; Nikolaj Thure Krarup; Britt Borregaard; Nikolai Uberg; Annette Høgh (BMC, 2024)
Abstract Background Bilateral blood pressure (BP) measurement is important in cardiovascular prevention for identifying systolic interarm BP difference (IAD) and hypertension. We investigated sex-stratified IAD prevalence and its associations and coexistence with screen-detected peripheral atherosclerosis and hypertension. Furthermore, we determined the proportion misclassified as non-hypertensive when using the lower versus the higher reading arm. Methods This sub-study formed part of the Viborg Screening Program (VISP), a cross-sectorial population-based cardiovascular screening programme targeting 67-year-old Danes. VISP includes screening for peripheral atherosclerosis (lower extremity arterial disease and carotid plaque), abdominal aortic aneurysm, hypertension, diabetes mellitus, and cardiac disease. Self-reported comorbidities, risk factors, and medication use were also collected. Among 4,602 attendees, 4,517 (82.1%) had eligible bilateral and repeated BP measurements. IAD was defined as a systolic BP difference ≥ 10 mmHg. IAD-associated factors (screening results and risk factors) were estimated by logistic regression; proportional coexistence was displayed by Venn diagrams (screening results). Results We included 2,220 women (49.2%) and 2,297 men (50.8%). IAD was more predominant in women (26.8%) than men (21.0%) (p < 0.001). This disparity persisted after adjustment [odds ratio (OR) 1.53; 95% confidence interval (CI) 1.32-1.77]. No other association was recorded with the conditions screened for, barring potential hypertension: BP 140-159/90-99 mmHg (OR 1.68, 95% CI 1.44-1.97) and BP ≥ 160/100 mmHg (OR 1.82, 95% CI 1.49-2.23). Overall, IAD and BP ≥ 160/100 mmHg coexistence was 4% in women and 5% in men; for BP ≥ 140/90 mmHg, 13% and 14%, respectively. Among those recording a mean BP ≥ 140/90 mmHg in the higher reading arm, 14.5% of women and 15.3% of men would be misclassified as non-hypertensive compared with the lowest reading arm. Conclusion Female sex was an independent factor of IAD prevalence but not associated with other arterial lesions. Approximately 15% needed reclassification according to BP ≥ 140/90 mmHg when the lower rather than the higher reading arm was used; verifying bilateral BP measurements improved detection of potential hypertension. In future, the predictive value of sex-stratified IAD should be assessed for cardiovascular events and death to verify its potential as a screening tool in population-based cardiovascular screening. Trial registration for VISP NCT03395509:10/12/2018.